2015
DOI: 10.1523/jneurosci.4208-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Costimulation of AMPA and Metabotropic Glutamate Receptors Underlies Phospholipase C Activation by Glutamate in Hippocampus

Abstract: Glutamate, a major neurotransmitter in the brain, activates ionotropic and metabotropic glutamate receptors (iGluRs and mGluRs, respectively). The two types of glutamate receptors interact with each other, as exemplified by the modulation of iGluRs by mGluRs. However, the other way of interaction (i.e., modulation of mGluRs by iGluRs) has not received much attention. In this study, we found that group I mGluR-specific agonist (RS)-3,5-dihydroxyphenylglycine (DHPG) alone is not sufficient to activate phospholip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…However, even this independent pathway would affect mGluR5 downstream. Evidence from other studies suggests that activation of the AMPA receptors leads to changes in the mGluR5 signaling and facilitation of downstream effects 58 , which could play a role in the current work. The exact mechanism leading to mGluR5 downregulation in the current study cannot be assessed with PET imaging; nonetheless, our data suggest that mGluR5 may play an important role in relieving symptoms of anxiety specifically.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…However, even this independent pathway would affect mGluR5 downstream. Evidence from other studies suggests that activation of the AMPA receptors leads to changes in the mGluR5 signaling and facilitation of downstream effects 58 , which could play a role in the current work. The exact mechanism leading to mGluR5 downregulation in the current study cannot be assessed with PET imaging; nonetheless, our data suggest that mGluR5 may play an important role in relieving symptoms of anxiety specifically.…”
Section: Discussionmentioning
confidence: 68%
“…The hypothesis is also in line with other recent studies demonstrating that activation of postsynaptic AMPA receptors is a critical component related to the rapid antidepressant-like effects associated with several additional compounds 56 , 57 . Evidence exists from other studies suggesting that activation of the AMPA receptors leads to changes in the mGluR5 signaling and facilitation of downstream effects 58 , which could play a role in the current work.…”
Section: Discussionmentioning
confidence: 73%
“…However, it is relevant to note that the molecular mechanisms seem to differ between brain regions. Indeed, in hippocampus, DHPG-LTD is considered to be independent of PLC/IP 3 pathway and postsynaptic Ca 2+ (Schnabel et al, 1999 ; Fitzjohn et al, 2001 ; Mockett et al, 2011 ; Kim et al, 2015 ), but there is also evidence of IP 3 mediated ER-Ca 2+ release from dendritic spines and calmodulin activation for group I mGluR LTD (Holbro et al, 2009 ; Sethna et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, hippocampal NMDAR-LTD and mGluR-LTD can be induced by bath application of NMDA and agonists of group I mGluRs, respectively [ 1 ]. Although LTDs induced by these agonists diverge many mechanistic aspects from the LFS-LTD [ 1 , 18 , 19 ], they occlude further induction of electrical LTDs and thus share them some underlying mechanisms of expression [ 3 , 20 ]. Moreover, chemical-LTD has the advantage of massive synaptic depression [ 21 ], which therefore maximizes the probability of detecting biochemical changes [ 22 ] and, in consequence, their sensitivity to interruption [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that generally LTD can be readily induced in acute hippocampal slices prepared from juvenile [ 17 , 20 ] or from adult rodents under specific conditions [ 17 , 24 ], but it is difficult to induce LTD in slices obtained from middle-aged or senescent rodents and, when observed [ 12 , 24 , 25 ], the recording intervals rarely showed LTD recorded for more than 4 h [ 12 ]. However, genetic knockout associated with enhancement of protein synthesis in old mice was associated with enhancement of ( RS )-3,5-dihydroxyphenylglycine (DHPG)-induced LTD, implying that the difficulty to induce LTD in wild-type old animals may be due to a physiological suppression of protein synthesis [ 26 ].…”
Section: Introductionmentioning
confidence: 99%